Role of Dectin-1 in peripheral nerve injury - Hsu, Angela Yu-Huey; Hsieh, Sung-Tsang (Frontiers in Cellular Neuroscience, 2022)
Dectin-1, a C-type lectin receptor, plays a role in nerve injury in the central nervous system. However, whether it plays a role in the peripheral nervous system is not well understood. Our study showed the expression of Dectin-1 on the membrane of macrophages. We also used a sciatic nerve crushing injury model to demonstrate that there was a delay in nerve degeneration-related processes such as breakdown of injured myelinated nerve fibers and formation of myelin ovoid in groups injected with whole glucan particle soluble (WGPS), a Dectin-1 antagonist. There were also fewer intraneural blood vessels in the Dectin-1 antagonist treated group. Our study suggested inhibiting Dectin-1 delayed debris clearance, nerve degeneration, and angiogenesis after peripheral nerve injury.